Integrating Community Expertise into the Academy: South Los Angeles’ Community-Academic Model for Partnered Research - del Pino, Homero E. (Prog Community Health Partnersh, 2016)
THE PROBLEM: Charles R. Drew University (CDU) and community partners wanted to create a structure to transcend traditional community–academic partnerships. They wanted community leaders integrated into CDU’s research goals and education of medical professionals. PURPOSE OF ARTICLE: To explain the establishment of the Community Faculty Program, a new model of community–academic partnership that integrates community and academic knowledge. KEY POINTS: Using CBPR principles, CDU and community partners re-conceptualized the faculty appointment process and established the Division of Community Engagement (DCE). CDU initially offered academic appointments to nine community leaders. Community Faculty contributes to CDU’s governance, education, research, and publication goals. This model engaged communities in translational research and transformed the education of future healthcare professionals. CONCLUSION: The Community Faculty Program is a new vision of partnership. Using a CBPR approach with committed partners, a Community Faculty Program can be created that embodies the values of both the community and the academy.